SOFTWARE DEVELOPMENT FOR OPTIMIZATION FOR SHELL AND TUBE HEAT EXCHANGER WITH BAT ALGORITHM - Richard Ricardo, Janvier
Heat exchanger is one of the mechanical components that can be found everywhere at present. Heat exchanger needs design procedure with some consideration so that design can be profitable, both in performance and economic aspect. Procedure of designing a heat exchanger can be achieved by optimization. The optimization is carried out by using Bat algorithm. This algorithm is a part of particle swarm optimization. This algorithm is utilizing the nature of bat to hunt down its prey. The principal used by bat is echolocation, which bat will be emitting some various pulse for heterogeneous emission and amplitude. This is done many times until the bat can find its prey. This study aims to design simple software using Bat Algorithm to optimize the total cost of heat exchanger by using the area of heat exchangers and pressure drop parameters. Those two parameters are divided into shell diameter, outer tube diameter, tube length, and baffle spacing variation. This optimization process assisted by using software that has been made. This software can be run and can be used as one of the tools to design a heat exchanger. The operation of this software is quite simple, only needed Command Prompt or other applications that can run syntax, and does not take a long time, between 3–5 seconds. This software also produces higher calculation accuracy compared to other software. Moreover, this software also presented in Bahasa which is quite understandable and the time to enter input is only 1 minute.